Stabilization of the structure butter pastes - Yatsenko, Olga; Yushchenko (Gonchar), Natalia; Bandura (Kuzmyk), Uliana (My University, 2019)
For foods characterized by high moisture content, it is necessary to ensure the proper structural and mechanical properties, organoleptic characteristics of the products and stability during storage for this requires the use of functional and technological ingredients. Purposeful combination allows to use the properties of separate components of multicomponent dairy products as efficiently as possible. Therefore, the development of stabilization systems for butterpastes as complex emulsion systems is relevant, as it will allow to obtain products with a given structure and increase the economic efficiency of production.
Keywords: стабілізаційна композиція; масляні пасти; stabilization composition; butters pastes; кафедра технології молока і молочних продуктів; кафедра технології ресторанної і аюрведичної продукції